Advertising and celebrity endorser on purchase intention k-poppers at tokopedia online shopping - Firda Luthfiya Hamida; Ayuningtyas Y Hapsari (Enrichment : Journal of Management, 2023)
The development of the current era of globalization has changed the pattern of life and human behavior to tend to shop online through various existing platforms, including e-commerce. Many things are done by e-commerce to attract consumers' attention, one of which is through the Brand Ambassador idol from South Korea. Tokopedia is one of the e-commerce companies that invited BTS and Blackpink to become Celebrity Endorses in 2021. Based on this, this study aims to see the influence of advertising and celebrity endorsers on buying interest of K-Poppers in online shopping at Tokopedia. This study used an associative quantitative approach with a total sample of 115 Tokopedia users using the Google form. The data analysis technique uses multiple linear regression analysis accompanied by partial tests (t-test) and simultaneous tests (F-test). Based on the results of the t-test, which are presented in the table above, the following information is obtained: The Advertising variable has a significance value of 0.000, less than 0.05. Meanwhile, the t count obtained a value of 4.884 > t table (1.9813). The Celebrity Endorser variable has a significance value of 0.000, less than 0.05. Meanwhile, the t count obtained a value of 5.435 > t table (1.9813). Thus, advertising and celebrity endorsers positively and significantly affect interest in buying online shopping at Tokopedia.